2011
DOI: 10.1016/j.jenvman.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hexavalent chromium removal in a continuous biological filter with the use of central composite design (CCD)

Abstract: Hexavalent chromium is frequently found in industrial effluents as a result of the industrial applications of this compound and its anti-corrosive features. However, hexavalent chromium is extremely toxic, and its discharge in water is regulated, with a maximum limit of 0.1 mg/L in accordance with legislation established by CONAMA-Brazil (no. 397, April 3, 2008). To achieve lower discharge values, it is necessary to reduce from Cr(VI) to Cr(III), which is less toxic, and an economic alternative involves biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Preliminary tests with industrial support media (Dalcin et al 2011) were not very efficient. Then we started a search for a support media that: (i) has the ability to remove high loads of organic and of Cr(VI) per unit volume; (ii) has a structure that was widely open, to avoid clogging by biomass growth and to ensure an adequate supply of oxygen, without the use of forced aeration; (iii) provides structural strength enough to support its own weight and the weight of the biomass that grows attached to its surface; (iv) was light enough to allow significant reductions in the cost of construction; (v) was biologically inert; so it would not be attacked by micro-organisms or toxic to the process; (vi) was chemically stable and presented the lowest possible cost per unit of organic matter removed.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Preliminary tests with industrial support media (Dalcin et al 2011) were not very efficient. Then we started a search for a support media that: (i) has the ability to remove high loads of organic and of Cr(VI) per unit volume; (ii) has a structure that was widely open, to avoid clogging by biomass growth and to ensure an adequate supply of oxygen, without the use of forced aeration; (iii) provides structural strength enough to support its own weight and the weight of the biomass that grows attached to its surface; (iv) was light enough to allow significant reductions in the cost of construction; (v) was biologically inert; so it would not be attacked by micro-organisms or toxic to the process; (vi) was chemically stable and presented the lowest possible cost per unit of organic matter removed.…”
Section: Methodsmentioning
confidence: 96%
“…Dermou et al (2005) analyzed the concentration of carbon during the reduction of 33 mg l -1 of hexavalent chromium, and found that 265, 150, and 20 mg l -1 of carbon were obtained after 40, 30, and 340 min of operation, respectively, in the complete reduction of 33 mg l -1 of Cr(VI). Dalcin et al (2011) studied the Cr(VI) removal in a continuous biological filter using CCD methodology with successfully. The analysis of the CCD showed that the initial hexavalent chromium concentration was the most significant variable in the process and the pH value also contributed to the rate of hexavalent chromium removal but to a lesser extent than the initial concentration of Cr(VI).…”
Section: Cr(vi) Bioremovalmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitness of the given models can be tested by ANOVA statistics (R 2 , adjusted R 2 , F-test and t-test) and residuals analysis. As Bezera et al [180] introduced RSM as a tool for optimization in analytical chemistry, this kind of design experiment has been widely used by different researchers in order to optimization of water and soil remediation [166,173,[181][182][183] or designing different types of water filters [184,185]. The experimental design and statistical analysis of the data were done by Design-expert10 statistical software.…”
Section: Simulating Testing Practice: Rsm Modelmentioning
confidence: 99%
“…Em pesquisas desenvolvidas na Faculdade de Engenharia Química da Universidade Federal de Uberlândia, utilizando meios sintéticos simulando um efluente de curtume, foi utilizada aplicação de campo magnético em micro-organismos de culturas mistas para redução de Cr(VI) a Cr(III) (Dalcin et al, 2011, Leles et al, 2012, Moura, 2012.…”
Section: Introductionunclassified